ANALISIS PERBANDINGAN KINERJA KEUANGAN PERUSAHAAN PERTAMBANGAN BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2017 - Mardiah Kenamon; Putra Deba Devara (Jurnal Akuntansi dan Keuangan, 2019)
This study aims to compare the financial performance of coal mining companies listed on the Indonesia Stock Exchange and to find out which financial performance is the best among coal mining companies listed on the Indonesia Stock Exchange. This study uses secondary data in the form of financial statements of PT. Adaro Energy Tbk, PT. Delta Dunia Makmur Tbk, PT. Resource Alam Indonesia Tbk, PT. Bukit Asam (PERSERO) Tbk and PT. Toba Bara Tbk 2013-2017 period. The analytical tool used in this study is a different test paired sample t-test and financial ratios consisting of liquidity ratios measured by current ratio, quick ratio and cash ratio, solvency ratios measured by debt to asset ratio, debt to equity ratio and long term debt to equity ratio, activity ratio measured by fixed assets turn over and total assets turn over and profitability ratios as measured by net profit margins, return on investment and return on equity. This research uses quantitative research. The results of research that have been conducted show that based on the comparison of the liquidity ratio can be seen that when viewed from the current ratio, PT. Delta Dunia Makmur Tbk has a better financial performance, when viewed from the quick ratio, PT. Bukit Asam (PERSERO) Tbk has a better financial performance and when viewed from the cash ratio, PT. Adaro Energy Tbk has better financial performance. Based on the comparison of solvency ratios consisting of debt to asset ratio, debt to equity ratio and long term debt to equity ratio, it can be seen that PT. Resource Alam Indonesia Tbk has better financial performance. Based on the ratio of activity ratios, it can be seen that when viewed from fixed assets turn over, PT. Resource Alam Indonesia Tbk has a better financial performance and when viewed from total assets turn over, PT. Toba Bara Tbk has better financial performance. Based on the comparison of profitability ratios consisting of net profit margin, return on investment and return on equity, it can be seen that PT. Bukit Asam (PERSERO) has better financial performance.